Education Relations, Number of Children and Acceptance of KB Information with Pregnancy Due to Unmet Need KB in Pregnant Mother in Binjai Health Center City In 2019 - Syawalina Syawalina; Heru Santosa; Sri Rahayu Sanusi (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
Pregnancy control and regulation is one of the ways to suppress the population in Indonesia through the family planning (KB) program. However, family planning programs in Indonesia still have problems, one of which is the high number of unmet need for family planning in Indonesia. 5 sub-districts in the City of Binjai showed that the District of Binjai Kota which had the highest number of unmet need for family planning was 18.27%. The purpose of this study was to analyze the Relationship of Education, Number of Children and Acceptance of Family Planning Information with Pregnancy Due to Unmet Need for KB in Pregnant Women in Binjai City Health Center in 2019. The method of this study used a cross sectional sample of 113 pregnant women in December 2018 - August 2019 at the Binjai City Health Center. Data were collected by interview using a questionnaire. Based on the results of the study note that out of 113 pregnant women there were 57 people (50.4%) who became pregnant as a result of Unmet Need KB. Variables related to Pregnancy Due to Unmet Need for KB are the number of children (p = 0.024) and the receipt of KB information (p = 0.001). The results of multiple logistic regression showed that respondents who had 1-2 children and did not receive family planning information had a probability of suffering from pregnancy due to unmet need for birth control by 57.8%. The suggestion for this research is that health workers pay more attention to those who have 1-2 children who are motivated to participate in the family planning program and ask pregnant women to ask health workers before using family planning tools as clearly as possible so that they are expected to be able to reduce the reasons for unmet need for family planning.